The forgotten or sidelined human right to leisure - Ulloa Millares, Daniel Augusto (2016)
The culture of presenteeism is deeply rooted in our labor practice and looks bad (or very bad) that an employee cease its work on time, calling uncommitted or “bureaucrat”, which is paradoxical because there are thousands of public servers that do not have a maximum working time. What is not assimilated is that working time is the opposite of free time, which all the hours you’re at work are hours when you do not have freedom to do other things (studying, going to the movies, spending time with family, etc.). And that can cause illness or even kill the employee. This paper seeks to reflect on this important subject in the lives of individuals.